Importance of harmonization of accounting and auditor qualification standards in the European Union with a comparisonal view of the situation in Türkiye and Turkish practice. - Urçar, Serdar (My University, 1994)
unknown
Keywords: Avrupa Topluluğu_Muhasebe; Muhasebe; Yönetim ve yardımcı hizmetler